Implementation of a Palm Oil Based Biofuel Policies in the Realization of Sustainable Development in Musi Banyuasin District - Iskandar Syahriyanto; Erliana Hasan; Udaya Madjid; Megandaru W. Kawuryan (Budapest International Research and Critics University, 2022)
This research intends to analyze the implementation of policies, factors that influence the implementation of oil palm-based biofuels in Musi Banyuasin District, to further formulate a model for implementing policies related to renewable energy. Research uses qualitative descriptive methods with an inductive approach. Research data obtained through interviews, observations and document tides. The results of the research findings were identified: 1) Implementation of the biofuel policy is quite good where the policy through the development program of the natural product processing industry and downstream industry, revitalization and replanting of plantation land, data collection on smallholder plantations, agrarian reform, and development pays attention to environmental impacts and climate change; 2) factors that influence the successful implementation of policies namely regional leadership determination, support from actors in the target environment. While the factors that influence the failure of policy implementation are the absence of SOPs, budget shortages, weak coordination, and uneven political will; and 3) The Sustainable Renewable Energy Policy Implementation Model consists of dimensions of the policy context, implementing context, policy objectives, and sustainability consensus.